1993
DOI: 10.1111/j.1365-2028.1993.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural changes and behavioural thermoregulation in Colobus polykomos: the effect of climate and diet

Abstract: SummaryColobine monkeys are widely reported to spend considerable portions of their daily activity budgets resting. To test the hypothesis that resting and associated postures are related to energy conservation and thermoregulation, resting behaviours in Colobus polykomos are examined in relation to vegetation cover, weather conditions and diet. Seasonal differences in hunching are shown to be significantly correlated with cool, wet conditions and low energy intake, while postures associated with heat dissipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…during the study 18.7°C, range 11-22, N = 415 nights), and the branches of tall, emergent trees seem relatively equally exposed to the elements (Smith et al 2007). However, like C. polykomos (Dasliva 1993), C. vellerosus slept sitting up, hunched over, with their limbs tucked in, perhaps to conserve heat (but this species spends most of its time during the day in a sitting position as well, Schubert 2011). The study groups also took longer to leave their sleeping sites after cooler nights, as has been noted for S. mystax and S. fuscicollis (Smith et al 2007), which may indicate that some sunbathing was necessary for the group to get active (Dasilva 1992(Dasilva , 1993.…”
Section: Discussionmentioning
confidence: 98%
“…during the study 18.7°C, range 11-22, N = 415 nights), and the branches of tall, emergent trees seem relatively equally exposed to the elements (Smith et al 2007). However, like C. polykomos (Dasliva 1993), C. vellerosus slept sitting up, hunched over, with their limbs tucked in, perhaps to conserve heat (but this species spends most of its time during the day in a sitting position as well, Schubert 2011). The study groups also took longer to leave their sleeping sites after cooler nights, as has been noted for S. mystax and S. fuscicollis (Smith et al 2007), which may indicate that some sunbathing was necessary for the group to get active (Dasilva 1992(Dasilva , 1993.…”
Section: Discussionmentioning
confidence: 98%
“…The logic of reducing thermoregulation costs seems to stand up independent of a "dislike of wet ground." Furthermore, behavior related to ambient temperature for thermoregulation was reported in several primate species: Lepilemur leucopus (Nash, 1998), Cercopithecus sabaeus (Harrison, 1985), Colobus polykomos (Dasilva, 1993), Macaca fuscata (Watanuki and Nakayama, 1993;Schino and Troisi, 1998), and Alouatta caraya (Bicca-Marques and CalegaroMarques, 1998); thus it appears to be a widespread pattern among primates.…”
Section: Comparison and Implications Of Ground Usementioning
confidence: 94%
“…A number of studies found primates to alter their activity in response to thermoregulatory needs, with a midday peak in resting thought to be a response to high ambient temperature (Stoltz and Saaymann, 1970;Bernstein, 1972Bernstein, , 1975Bernstein, , 1976. Conversely, other studies found low temperature to be associated with increased feeding activity (Iwamoto and Dunbar, 1983), huddling (Ostner, 2002), postural changes (Stelzner and Hausfater, 1986;Dasilva, 1993), and mother-infant contact (Brent et al, 2003). Recent studies also suggested that temperature plays a role in the terrestrial behavior of chimpanzees (Takemoto, 2004) and habitual cave use by chacma baboons .…”
mentioning
confidence: 91%